Electronic Matching of HIV/AIDS and Hepatitis C Surveillance Registries in Three States - Speers, Suzanne (Association of Schools of Public Health, 2011)
OBJECTIVES: Both HIV and hepatitis C virus (HCV) can be transmitted through percutaneous exposure to blood in similar high-risk populations. HCV and HIV/AIDS surveillance databases were matched in Colorado, Connecticut, and Oregon to measure the frequency of co-infection and to characterize co-infected people. METHODS: We defined a case of HCV infection as a person with a reactive antibody for hepatitis C, medical diagnosis, positive viral-load test result, or positive genotype reported to any of three state health departments from the start of each state’s hepatitis C registry through June 30, 2008. We defined a case of HIV/AIDS as a person diagnosed and living with HIV/AIDS at the start of each state’s respective hepatitis C registry through June 30, 2008. HIV/AIDS and hepatitis C datasets were matched using Link King, public domain record linkage and consolidation software, and all potential matches were manually reviewed before acceptance as a match. RESULTS: The proportion of reported hepatitis C cases co-infected with HIV/AIDS was 1.8% in Oregon, 1.9% in Colorado, and 4.9% in Connecticut. Conversely, the proportion of HIV/AIDS cases co-infected with hepatitis C was consistently higher in the three states: 4.4% in Oregon, 9.7% in Colorado, and 23.6% in Connecticut. CONCLUSIONS: Electronic matching of registries is a potentially useful and efficient way to transfer information from one registry to another. In addition, it can provide a measure of the public health burden of HIV/AIDS and hepatitis C co-infection and provide insight into prevention and medical care needs for respective states.